Causal Effects of Smoking, Alcohol, Coffee, and Tea Intake on Gynecologic Cancers: A Mendelian Randomization Study - Miao J; Xu Y (International Journal of Women's Health, 2025)
Jiayan Miao, Yuexin Xu Department of Obstetrics and Gynecology, Nanjing Maternal and Child Health Hospital, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Yuexin Xu, Email 2513510533@qq.comObjective: The two-sample Mendelian randomization (MR) approach was used to evaluate the causal association between modifiable lifestyle and gynecological tumors.Methods: Based on publicly accessible summary level genome-wide association study (GWAS), the exposures were age of smoking initiation, cigarettes per day, smoking cessation, smoking initiation, alcohol intake, tea intake, coffee intake, and the outcomes were cervical, ovarian and endometrial cancer. IVW, MR-Egger, WM, Weighted Mode and Simple Mode method were used to evaluate the causal relationship, and sensitivity analysis, heterogeneity analysis and heterogeneity analysis were performed.Results: Smoking initiation (OR: 1.186, 95% CI: 1.009– 1.394, P= 0.040) and alcohol intake (OR: 1.235, 95% CI: 1.063– 1.436, P= 0.010) increased the risk of ovarian cancer, smoking cessation (OR: 0.636, 95% CI: 0.441– 0.917, P= 0.020) was a protective factor for endometrial cancer, while alcohol intake (OR: 1.262, 95% CI: 1.051– 1.517, P= 0.010) was a risk factor for endometrial cancer. Cigarettes per day (OR: 1.004, 95% CI: 1.001– 1.007, P= 0.000) and smoking initiation (OR: 1.003, 95% CI: 1.001– 1.005, P= 0.000) both increase the risk of cervical cancer. The sensitivity analysis of each group showed robust results, no pleiotropy was found, and there were no abnormal variables in the heterogeneity test.Conclusion: Smoking and alcohol intake are causally linked to gynecological tumors, whereas the tea and coffee intake do not exhibit a causal association with gynecological tumors.Keywords: lifestyle, cervical cancer, ovarian cancer, endometrial cancer, Mendelian randomization